2022
DOI: 10.1111/cdev.13820
|View full text |Cite
|
Sign up to set email alerts
|

Development of information integration in the visual working memory of preschoolers

Abstract: Visual working memory (WM) plays a pivotal role in integrating fragments into meaningful units, but no study has addressed how visual WM integration takes place in children. The current study examined whether WM integration emerges once preschoolers master Gestalt cue and can retain two representations in WM (automatic integration hypothesis), or still needs time to mature (maturation‐of‐integration hypothesis). Four experiments (N = 168, 81 females, 4‐ to 6‐year‐olds, Chinese, in Hangzhou, China, from 2016.10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…Still, performance on the latter two tasks did not correlate. This finding indicated that working memory might serve as a “foundation” for successful performance in cognitive shifting and inhibitory control tasks, which require the children to maintain and manipulate the rules in mind [ 64 ]. First, for the cognitive shifting task, even though memory demands were minimized by the experimenter reminding the participants of the current sorting criterion on each trial [ 65 ], they almost succeeded in the switching task (mean correct rate of 97%); it seems that cognitive shifting required working memory in addition to the ability to shift.…”
Section: Discussionmentioning
confidence: 99%
“…Still, performance on the latter two tasks did not correlate. This finding indicated that working memory might serve as a “foundation” for successful performance in cognitive shifting and inhibitory control tasks, which require the children to maintain and manipulate the rules in mind [ 64 ]. First, for the cognitive shifting task, even though memory demands were minimized by the experimenter reminding the participants of the current sorting criterion on each trial [ 65 ], they almost succeeded in the switching task (mean correct rate of 97%); it seems that cognitive shifting required working memory in addition to the ability to shift.…”
Section: Discussionmentioning
confidence: 99%